Estudio limnológico de Laguna Blanca Chica (Olavarría, provincia de Buenos Aires) durante un período de sequía - Sanzano, Pablo (2014)
The aquatic ecosystems of the Pampean plains usually have highly variable dynamics which affects the abundance of fish resources. We analyzed Blanca Chica shallow lake located in the central region of the province of Buenos Aires. It has neither tributaries nor effluents. It hosts sport fishing, water sports without engine, and its surroundings are used for recreation. Here we report the effects of drought in the structure and functioning of the shallow lake, with emphasis on the fish community. Limnological and ichthyologic analyses were carried out in 2007, 2008, 2011 (year characterized by extreme regional dry period) and 2014. In 2007 the phytoplankton was dominated by Botryococcus braunii. Pejerrey (Odontesthes bonariensis) was dominant in the fish samples, but showing an important decrease in numbers and biomass. Catch per unit effort (CPUE) was low and showed poor fish quality with high taeniasis. In 2008, zooplankton improved both in quality and quantity and became the basis of pejerrey`s diet, which effectively increased its abundance and its biomass, with fish in the 1- and 2-year class. In 2011 the conductivity, chlorophyll-a, chlorides, sodium, ammonium and sulfates were one order of magnitude above historical values. The extreme limnological conditions and notorious area reduction triggered a total absence of fish. The 2014 campaign showed that the shallow lake level had increased from 1,5 to 2 m. However, no fish were detected; the absence may be explained by the lake’s isolation and natural massive mortality occurred.